Centres in Social Science Research Methodology - Planning Commission (Planning Commission, Government of India, 1961)
The document “Centres in Social Science Research Methodology,” prepared by the Planning Commission’s Research Programmes Committee, outlines a landmark initiative launched in 1954 with financial support from a $500,000 Ford Foundation grant to strengthen applied social science research training in Indian universities. The program aimed to build a strong foundation of qualified social scientists capable of addressing India’s developmental challenges by establishing specialized research centers at six universities—Bombay, Poona, Delhi, Madras, Punjab, and Utkal—each focusing on areas aligned with national economic priorities. Structured around advanced doctoral training, seminars for MA students, and participation by college lecturers, the centers emphasized rigorous methodological instruction, statistical competence, survey techniques, and scientific research design. Fortnightly seminars, engagement with visiting scholars, and well-equipped libraries supported academic development, while extensive fieldwork projects provided practical research experience culminating in data analysis, seminar presentations, and published monographs. Although implementation timelines varied across centers, the initiative received positive evaluations and demonstrated significant progress in enhancing research capacity. Subsequent recommendations included consolidating experiences through national seminars, drafting a comprehensive syllabus for research methodology, and integrating structured methodology training into university curricula. Overall, the document highlights the strategic importance of systematic research training in fostering scholarly excellence and strengthening India’s capacity to address complex social and economic issues through evidence-based inquiry.
Planning Commission Research Programmes Committee August, 1961
Keywords: Social Science Research Methodology; Planning Commission; Research Programmes Committee; Ford Foundation Grant; University Research Centres; Doctoral Training; Applied Social Science Research; Research Fellowships; Fieldwork and Monographs; Statistical Analysis; Survey Design; Curriculum Development